A cryogen-free HTS Josephson junction detector for terahertz imaging. (6th July 2015) - Du, J; Smart, K; Li, L; Leslie, K E; Hanham, S M; Wang, D H C; Foley, C P; Ji, F; Li, X D; Zeng, D Z
Abstract: A cryogen-free terahertz (THz) imaging system based on a high-temperature superconducting (HTS) Josephson junction detector is reported. The detector was made of a YBa2 Cu3 O7− x step-edge Josephson junction and integrated into an on-chip thin-film antenna. The HTS Josephson detector was cooled via a commercial mechanical cryocooler; an important step towards cryogen-free THz instrumentation, which is critical for industrial acceptance. In addition, it is shown that operating the detector in a cryocooler provides improved flexibility for optimizing the detector parameters and performance due to the ability to adjust the temperature compared to liquid nitrogen cooling methods. The dc and ac characteristics, the detector responsivity and the noise-equivalent power of the detector, and resulting image quality were studied as the function of operating temperatures.